A simplified approach to evaluate the lung cancer risk related to airborne particles emitted by indoor sources. (15th October 2021) - Caracci, E.; Stabile, L.; Buonanno, G.
Abstract: Indoor particle sources are recognized as detrimental for indoor air quality. Indeed, the high emission rates of the different aerosol metrics and carcinogenic compounds can lead to a high lung cancer risk for people exposed in indoor environments. A-priori lung cancer risk assessments could be very helpful to identify critical environments and sources, but they need complex and site-specific experimental analyses in order to measure particle concentration levels and chemical compositions. Thus, simplified assessments for lung cancer risks are highly welcomed. In the present paper, a simplified approach aiming at evaluating the lung cancer risk related to airborne particles emitted is proposed and applied to different indoor sources. The approach is based on the combination of (i) a recently developed approach to estimate the "emitted risk" of indoor particle sources and (ii) an easy-to-use mass balance equation to calculate the indoor "risk concentration" due to such emitted risk in an indoor environment. Simulations considering different scenarios in terms of previously characterized sources, ventilation rates, and exposure mitigation solutions were performed. The results show that the "risk emitted" is mostly related to sub-micron particles (with respect to super-micron ones) and that the lung cancer risk received by people in indoor environments can be extremely high for different sources, e.g. cooking activities. The ventilation rates of residential environments are not able to appreciably reduce the risk, whereas extraction hoods and air purifiers can significantly decrease it. Highlights: Evaluation and application of an emitted risk approach to indoor particle sources. Predictive assessment of lung cancer risk for people exposed in indoor environments. The emitted risk is mostly related to sub-micron particles. The highest emitted risk is related to cooking activities. Extraction hoods and air purifiers can significantly decrease the risk.